Entrepreneurial Marketing And SMEs Growth In Post Covid-19 Era In Awka, Anambra State, Nigeria - Fabian Anoke; Nzewi Hope Ngozi; Eze Solomon Uchechukwu; Igwebuike Joyce (International Journal of Financial, Accounting, and Management, 2022)
Purpose: This study aimed at examining the effect of entrepreneurial marketing on SMEs growth in the post- Covid-19 Era in Awka Anambra State Nigeria. Research methodology: The study adopted a qualitative research design with five participants. An in-depth interview was used to elicit relevant information from the respondents. Data generated were carefully transcribed, reviewed, and harmonized. Thematic categories were created and categorized into two major themes- technological-driven marketing and need-oriented entrepreneurial marketing. Results: The study revealed that need-oriented marketing and technology-driven marketing are pivotal to the growth and sustainability of SMEs in the post-Covid-19 Era. Limitations: The restriction on gathering of people more than ten by the State Government due to the Covid-19 limited our study as the researchers would have loved to have a group and interactive decisions with the participants. Contribution: The result of this study will serve as an eye-opener to Nigerian policymakers and SME operators to key into modern entrepreneurial marketing tools and selvage her already depressed economy.